DESKRIPSI KETERAMPILAN PROSES SAINS MAHASISWA PENDIDIKAN KIMIA FKIP UNTAN PADA MATERI SIFAT KOLIGATIF LARUTAN - Nur Sakinah; Rachmat Sahputra; Rody Putra (Universitas Tanjungpura, 2018)
AbstractThis research was conducted to answer the problem of how science process skill of students of chemistry education FKIP UNTAN, Pontianak on the material properties of characteristic of colligative solution so that the purpose of this research is to describe the science process skill of students of chemistry education FKIP UNTAN, Pontianak on the material properties of characteristic of colligative solution. The subject of these studies amounted to 43 students of chemistry education courses of Basic Chemistry II 2015-2016 force. The form of this research uses descriptive research to describe the science process skill of the students. Research instrument used the science process skill test with indicators of asking questions, making hypotheses, analyze the data, and conclude. Data collecting technique used in this research is the measurement technique and direct communication. The results of the prosessing of data showed that the average science process skill of students every indicator on asking question, making hypotheses, analyze the data, and concluded of 77%, 50%, 42%, and 42% expectively, while the average science process skills every student including highly skilled, skilled, less skilled, and unskilled of 9%, 53%, 21%, and 16% expectively. Keywords: Science Process Skill, Solution Colligative Properties